Implementasi Hukum Tata Negara Darurat Dalam Kondisi Darurat Moneter Tahun 1998 Di Indonesia - Rahmadhona, Rahmadhona; Leonardo, Ayyub; Darmawan, Alifia Ridianti (Jurnal Konstitusi & Demokrasi, 2024)
In the process of transitioning the leadership of the Republic of Indonesia from President Soeharto to the leadership of President B.J. Habibie, there was a massive mass movement in mid-1997 to 1998. The impact of this monetary crisis on Indonesia was considered quite bad, because this monetary crisis also triggered other crises such as political crises and social economic crises so that the stability of the country was threatened from all fields. This study aims to map the condition of Indonesia during the 1998 monetary crisis, analyze the causes and impacts of the 1998 monetary crisis, and discuss the emergency policies set in order to assist efforts to overcome the monetary crisis in Indonesia. Using a qualitative approach through analysis of secondary data from government policies, international institutions, and academic literature, this study found that the crisis was caused by a combination of internal factors such as a weak banking system and fiscal deficits, with external factors such as currency speculation and foreign capital withdrawal. The government's response to the crisis was complex, starting from internal recovery from the banking sector and through the social net, to collaboration with the International Monetary Fund (IMF). These measures are expected to put Indonesia back on its feet economically, socially and politically.